1997
DOI: 10.1111/j.1752-7325.1997.tb02978.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Beliefs about Orthodontic Treatment: A Questionnaire Approach

Abstract: The questionnaire developed in the present study was found to be practical and reliable for use with providers and consumers of orthodontic care and can be used to explore factors affecting the demand for orthodontic care. Implications of possible unrealistic treatment expectations on the part of orthodontists and parents also are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 16 publications
7
61
0
Order By: Relevance
“…The overall high value placed on treatment suggests that parents greatly value the benefits they believe orthodontic therapy will offer. 25 Moreover, conflicting attitudes between adolescents and family members may be resolved during orthodontic counseling. 28 Responsiveness is the ability of a measure to detect clinical change when the patient's situation improves or deteriorates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall high value placed on treatment suggests that parents greatly value the benefits they believe orthodontic therapy will offer. 25 Moreover, conflicting attitudes between adolescents and family members may be resolved during orthodontic counseling. 28 Responsiveness is the ability of a measure to detect clinical change when the patient's situation improves or deteriorates.…”
Section: Discussionmentioning
confidence: 99%
“…Parents/caregivers also expect a considerable improvement in the social confidence of their adolescent sons and daughters as a result of orthodontic therapy. 25,26 Moreover, parental support and control are the most important constructs of family environment. Evidence strongly suggests that parental support exerts a considerable causal effect on an adolescent's response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…psychosocial impact of dental aesthetics), (29) or the impact of pain during treatment on quality of life. (30) Moreover, previously published valid and reliable questionnaires have limitations, for example some of these questionnaires are age specific (28)(29)(30)(31)(32)(33)(34)(35)(36). Other limitations are related to the aims of existing questionnaires developed for cross-sectional use to measure either motivation, expectations, experiences, or satisfaction (28-37).…”
Section: Comparison With Other Questionnairesmentioning
confidence: 99%
“…With regard to the validation methods, some studies have depended solely on face validity (31,32,34,35,37), which may not be robust enough to fully assess the validity of questionnaires when compared to the content validity process. Mandall et al (33) assumed their questionnaire measuring the impact of fixed appliance on daily life as having face and content validity; however, this was based only on the method of development without using any formal validity assessment.…”
Section: Comparison With Other Questionnairesmentioning
confidence: 99%
“…Orthodontics is defined as branch of dentistry that deals with correction of malocclusion, in order, w h e n e v e r p o s s i b l e ; t o a c h i e v e functionally appropriate occlusion and optimum dental and facial aesthetics Previous studies have revealed that patient/parent expectations from orthodontic treatments are to get better facial or dental appearance, dental health and oral function 13,14 . Improvement of Descriptive analysis was done and total number and percentages were presented.…”
Section: Introductionmentioning
confidence: 99%